2009
DOI: 10.1093/pasj/61.4.805
|View full text |Cite
|
Sign up to set email alerts
|

Energy Spectra of the Soft X-Ray Diffuse Emission in Fourteen Fields Observed with Suzaku

Abstract: The soft diffuse X-ray emission of twelve fields observed with Suzaku are presented together with two additional fields from previous analyses. All have galactic longitudes 65$^\circ $$\lt$$\ell$$\lt$ 295$^\circ $ to avoid contributions from the very bright diffuse source that extends at least 30$^\circ $ from the Galactic center. The surface brightnesses of the Suzaku nine fields for which apparently uncontaminated ROSAT All Sky Survey (RASS) were available were statistically consistent with the RASS values, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
160
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 41 publications
29
160
5
Order By: Relevance
“…Ne overabundance, together with Fe overabundance, was also reported by Yoshino et al (2009). In our analysis, however, we could not constrain the Fe abundance and we have been forced to set it at Fe/O=1 solar.…”
Section: The Excess Emissionmentioning
confidence: 58%
See 1 more Smart Citation
“…Ne overabundance, together with Fe overabundance, was also reported by Yoshino et al (2009). In our analysis, however, we could not constrain the Fe abundance and we have been forced to set it at Fe/O=1 solar.…”
Section: The Excess Emissionmentioning
confidence: 58%
“…This excess emission can be explained as an overabundance of Ne and/or Fe (Yoshino et al 2009) or as the presence of an additional warmer thermal component. Both cases have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…We checked the observation for contamination by solar wind charge exchange. The ACE SWEPAM 1 proton flux was less than 4 × 10 8 protons s −1 cm −2 which is typical of the quiescent Sun (e.g., Snowden et al 2004;Fujimoto et al 2007;Yoshino et al 2009), and the light curve accumulated in a 0.5−2 keV energy band (after soft proton flares removal) did not show any variability. The spectra of the out-of-field-of-view events of CCD 4 and 5 of MOS1 and CCD 5 of MOS 2 showed an anomalously high flux in the soft band (see ) so they were therefore excluded from our analysis.…”
Section: Observation and Data Reductionmentioning
confidence: 91%
“…Yoshino et al (2009) studied the soft, diffuse X-ray emission in 12 fields observed with the Suzaku X-ray Telescope. The Galactic longitudes and latitudes are similar to those XMM fields, i.e., high latitudes and away from the direction of the Galactic center, except two fields at b = 10…”
Section: Observational Constraintsmentioning
confidence: 99%